2014
DOI: 10.1002/chem.201304914
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Semiconducting Bispyrrolothiophenes for Organic Field‐Effect Transistors

Abstract: A series of new highly soluble bispyrrolothiophenes were synthesized from vinyl azides by using transition-metal-catalyzed C-H-bond functionalization. In addition to modifying the substituents present on the end-pyrrolothiophene moieties, the arene linker in between the two units was also varied. The solution-state properties and field-effect-transistor (FET) electrical behavior of these bispyrrolothiophenes was compared. Our investigations identified that the optical properties and oxidation potential of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 146 publications
0
16
0
Order By: Relevance
“… These investigations have established chemoselectivity trends, which permit the use of these C–H bond aminations in target-oriented syntheses . In contrast, these preferences remain unknown for metal N -aryl nitrenes despite the prevalence of the resulting aryl amines and N -heteroaromatics in pharmaceuticals and materials. As an additional complication, metal N -aryl nitrenes also react with adjacent π-systems through electrocyclization processes to produce N -heteroaromatics . Understanding and controlling the reactivity of metal N -aryl nitrenes to participate in an electrocyclization or C–H bond amination reaction is critical to the rational design of target-oriented syntheses that use this reaction at a late stage to install the valuable N -aryl moiety, which is ubiquitous in indole alkaloids, as well as the design of new reactions that harness the reactivity of metal N -aryl nitrenes.…”
Section: Introductionmentioning
confidence: 99%
“… These investigations have established chemoselectivity trends, which permit the use of these C–H bond aminations in target-oriented syntheses . In contrast, these preferences remain unknown for metal N -aryl nitrenes despite the prevalence of the resulting aryl amines and N -heteroaromatics in pharmaceuticals and materials. As an additional complication, metal N -aryl nitrenes also react with adjacent π-systems through electrocyclization processes to produce N -heteroaromatics . Understanding and controlling the reactivity of metal N -aryl nitrenes to participate in an electrocyclization or C–H bond amination reaction is critical to the rational design of target-oriented syntheses that use this reaction at a late stage to install the valuable N -aryl moiety, which is ubiquitous in indole alkaloids, as well as the design of new reactions that harness the reactivity of metal N -aryl nitrenes.…”
Section: Introductionmentioning
confidence: 99%
“…Upon polymerizing highly electron rich TP with electron deficient DPP, intermolecular interactions are expected to enhance by reducing the distance between polymer chains. ,− One of the concerns of employing electron rich pyrrole monomers is the high reactivity which can cause oxidization and degradation. Although pyrrole has a low ionization potential, previous reports of small molecules containing TP have shown HOMO levels below 4.8 eV . In our group, we have previously demonstrated that TP monomer is stable enough for electronic applications and it has the potential to be one of the high performing semiconductor building blocks for solution processable small molecule OFETs .…”
mentioning
confidence: 79%
“…Although pyrrole has a low ionization potential, previous reports of small molecules containing TP have shown HOMO levels below 4.8 eV. 52 In our group, we have previously demonstrated that TP monomer is stable enough for electronic applications and it has the potential to be one of the high performing semiconductor building blocks for solution processable small molecule OFETs. 53 Small molecules were synthesized, however, by intentionally functionalizing the 5 position of TP with an ester group.…”
mentioning
confidence: 84%
“…He is currently Chief Scientific Officer, Polyera Corporation, and Adjunct Professor of Chemistry at Northwestern University. Facchetti's research interests include organic photovoltaics, and optoelectronic materials and devices …”
Section: Awarded …mentioning
confidence: 99%